Implementation of a nurse-led alternate care site for the management of the surge of patients with COVID-19 in an Italian emergency department. Issue 7 (23rd March 2022) - Paganini, Matteo; Pizzato, Michele; Weinstein, Eric; Vecchiato, Elena; Bitetti, Andrea; Compostella, Caterina; Onesto, Caterina; Favaro, Andrea
Abstract : Background: To accommodate and separate the large numbers of patients going to hospital with COVID-19, many EDs had to create new pathways for patients. We describe the outcomes of patients treated in a nurse-led alternate care site (ACS) at our hospital. Methods: This was a retrospective study of outcomes of patients managed at the ACS of 'San Bassiano' Hospital ED, Bassano del Grappa, Italy between 9 March and 16 April 2020. Self-presenting patients aged 5 years and older, suspected of having COVID-19, were initially diverted to the ACS. Patients with a National Early Warning Score ≥5 or with a desaturation ≥4% after the walking test were sent back to the main ED COVID-19 path for further evaluation and medical attention and were not further followed up. In the ACS, patients received a CXR, blood samples and a nasopharyngeal swab to test for SARS-CoV-2, and were sent home. An emergency physician reviewed the results later and called the patient back 5–6 hours later with instructions to return for medical evaluation of abnormal findings, or to seek their general practitioner's attention. Patients received a follow-up phone call 15 days later to learn of their course. Results: A total of 487 patients were fully managed in the ACS and discharged home. Of the 392 (80.5%) patients with no abnormalities after the workup and instructed to stay at home, 29 reattended the ED in the next 15 days, and 13 were admitted. Among the 95 patients asked to return and receive medical attention, 20 were admitted and of those discharged, 3 reattended the ED within 15 days. At 15 days, no patient was deceased or received invasive ventilation; one admitted patient received non-invasive ventilation. Conclusions: A nurse-led ACS diverted a substantial proportion of patients from main ED resources without associated negative clinical outcomes.